Angiotensin-Converting Enzyme Inhibitor–based Versus Angiotensin Receptor Blocker–based Optimal Medical Therapy After Percutaneous Coronary Intervention: A Nationwide Cohort Study. Issue 1 (January 2021) - Park, Sangwoo; Kim, Yong-Giun; Ann, Soe Hee; Park, Hyun Woo; Suh, Jon; Roh, Jae-Hyung; Cho, Young-Rak; Han, Seungbong; Park, Gyung-Min
Abstract : Abstract: Optimal medical therapy (OMT) plays a crucial role in the secondary prevention of established coronary artery disease. The renin–angiotensin system (RAS) is an important target of OMT. However, there is limited evidence on whether there is any difference in the combined effect of OMT according to the classes of RAS blockade [angiotensin-converting enzyme inhibitor (ACEI) vs. angiotensin receptor blocker (ARB)]. Based on the nationwide National Health Insurance database in South Korea, 39, 096 patients who received OMT after percutaneous coronary intervention between July 2013 and June 2017 were enrolled. Patients were stratified into either acute myocardial infarction (AMI) or angina cohort and analyzed according to the class of RAS blockade included in OMT at discharge (ACEI vs. ARB). The primary end point was all-cause mortality. The study population had a median follow-up of 2.3 years (interquartile range, 1.3–3.3 years). In the propensity score-matched AMI cohort (8219 pairs), the risk for all-cause mortality was significantly lower in patients with ACEI-based OMT than in those with ARB-based OMT (hazard ratio 0.83 of ACEI, 95% confidence interval 0.73–0.94, P = 0.003). However, in the propensity score-matched angina cohort (6693 pairs), the mortality risk was comparable, regardless of the class of RAS blockade (hazard ratio 1.13, 95 confidence interval 0.99–1.29, P = 0.08). In conclusion, in this nationwide cohort study involving patients receiving OMT after percutaneous coronary intervention, ACEI-based OMT was associated with a significantly lower risk of all-cause mortality in patients with AMI in comparison with ARB, but not in those with angina. Abstract : Supplemental Digital Content is Available in the Text.